2007
DOI: 10.3354/cr034083
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting hare–lynx dynamics in the classic time series of the Hudson Bay Company, Canada

Abstract: Resale or republication not permitted without written consent of the publisher OPEN PEN ACCESS CCESSHare-lynx dynamics is determined by intrinsic self-regulation, and by the El Niño Southern Oscillation (ENSO). Photo: Tom and Pat Leeson

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 32 publications
1
33
0
1
Order By: Relevance
“…These indices are useful as they collapse multiple aspects of the physical environment, including ocean currents and air and water temperature, wave height, salinity, wind, and rainfall into a single parameter, and are thus generalizable ''phenomena'' rather than definable changes in single environmental variables (Stenseth et al 2002, Hallett et al 2004, Zhang et al 2007. Moreover, these studies have shown that such large-scale indices can serve as more effective indicators of ecological response than individual weather parameters collected at the scale of the organism (Stenseth 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These indices are useful as they collapse multiple aspects of the physical environment, including ocean currents and air and water temperature, wave height, salinity, wind, and rainfall into a single parameter, and are thus generalizable ''phenomena'' rather than definable changes in single environmental variables (Stenseth et al 2002, Hallett et al 2004, Zhang et al 2007. Moreover, these studies have shown that such large-scale indices can serve as more effective indicators of ecological response than individual weather parameters collected at the scale of the organism (Stenseth 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Stenseth et al 2004b). Zhang et al (2007) extend these studies by showing that another prominent climate pattern, the El Niño Southern Oscillation (ENSO), also plays a key role in the dynamics of the hare-lynx system. By so doing, they suggest that the structuring of the ecological dynamics might be more complicated than originally envisioned by Stenseth et al (1999), who suggested that regional differences in climate driven by the NAO resulted in a geographic grouping of lynx population dynamics.…”
mentioning
confidence: 59%
“…It is currently known that the hare resources growth model (in this case, a plant) has to be included in the system. Keith (1974), created the plant-hare-lynx hypothesis but the cycle determinants are still under study (Krebs et al, 2001, Zhang et al 2007.…”
Section: Developmentmentioning
confidence: 99%